2019
DOI: 10.32604/jrm.2019.07838
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Xyloglucan Molar Mass on Rheological Properties of Cellulose Nanocrystal/Xyloglucan Hydrogels

Abstract: Plant components are an inexhaustible source for the construction of bio-based materials. Here we report, for the first time, the elaboration of biobased cellulose nanocrystals (CNC)/xyloglucan (XG) hydrogels. XG is a hemicellulose displaying a great affinity for cellulose surface and can be thus irreversibly adsorbed on CNC. Properties of the hydrogels were investigated by varying the molar mass of XG either by enzymatic treatment with Endoglucanase (EG2) or physical fractionation by ultrasound (US). Fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The change from lamellar to alveolar morphology in the presence of XG has been related to an increase in the viscosity of the CNC/XG colloidal dispersion. 40 Accordingly, we recently reported that simple mixing of XG and CNC leads to an increase of the viscosity of the dispersion and the formation of hydrogels (Talantikite, Gourlay, Gall, & Cathala, 2019). We have proposed that gelation is due to steric stabilization when the CNC surface are crowded while cross-linking might occur at lower CNC/XG to form microgels in agreement with our previous reports (Dammak et al, 2015;Villares et al, 2015).…”
Section: Aerogels Morphologysupporting
confidence: 79%
“…The change from lamellar to alveolar morphology in the presence of XG has been related to an increase in the viscosity of the CNC/XG colloidal dispersion. 40 Accordingly, we recently reported that simple mixing of XG and CNC leads to an increase of the viscosity of the dispersion and the formation of hydrogels (Talantikite, Gourlay, Gall, & Cathala, 2019). We have proposed that gelation is due to steric stabilization when the CNC surface are crowded while cross-linking might occur at lower CNC/XG to form microgels in agreement with our previous reports (Dammak et al, 2015;Villares et al, 2015).…”
Section: Aerogels Morphologysupporting
confidence: 79%
“…Tamarind seed XG was subjected to ultrasonic treatment to obtain XG with a reduced molar mass. , Ultrasonic treatment was performed on 800 mL (separated into 4 × 200 mL batches) of a 1 wt % solution of XG using a QSonica Q700 probe sonication device (Q700, 230 V, 700 W, 20 kHz; Qsonica, Newtown, CT, USA). Sonication was performed for 40 min at a maximum amplitude of 25% (8 rounds of 5 min) with the sample submerged in an ice bath to prevent sample degradation from overheating.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has employed plant cell wall mimics to better understand the role of the XG structure on its capacity to bind to cellulose. ,,, Specifically, XG has been modified by altering the MW or degree of substitution of different saccharide residues through physical, chemical, or enzymatic treatments, and the adsorption to model cellulose films has been quantified. , It was found that at low MW, XG forms extended conformations on the surface of cellulose, forming closely packed sandwich structures between cellulose fibrils. , Conversely, high MW XG tends to form “loops and tails” between cellulose, which increases matrix swelling during hydration and is more accessible to enzymatic degradation. , XG saccharide residues are known to affect XG self-association and adsorption to cellulose. ,, The amount of fucosyl and galactosyl residues of XG were altered by selective enzymatic degradation, and while removal of fucosyl residues did not have a significant impact on adsorption to cellulose, removal of galactose groups (by 20–50%) resulted in strong self-association of XG, forming a reversible, thermoresponsive gel. , XG with fewer galactose groups also showed a higher mass adsorption onto cellulose than unmodified XG, forming a more compact structure. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, lignocellulosic biomass can be used for the production of hydrogels [ 101 , 102 ], but the properties of hydrogels have been shown to be affected by changes in the XyG structure. For example, the enzymatic removal of galactosyl side chains from the XyG backbone in biomass was shown to increased gelation and gel strength [ 101 , 103 ]. In Arabidopsis, β-Galactosidase 10 (AtBGAL10) was shown to be responsible for the majority of β-galactosidase activity against XyG, and its absence significantly altered XyG composition and plant growth [ 104 ].…”
Section: Lignocellulosic Biomass Chemical Constituentsmentioning
confidence: 99%